A Programming Model for the Determination of Benefits Obtainable from the Management of Open-Water Inland (Riverine) Fisheries of Bangladesh - Ahmed, K. M. Mahfuzuddin (1989)
In Bangladesh, most of the inland open-water fisheries had retained an open-access character in the absence of a consistent and effective management policy. Consequently the resulting pattern of fishing activities is characterised by economic inefficiency. In view of this, the current concern of the Government is to increase economic performance of the industry through some direct measures of control on the allocation of fishing rights, fishing effort and fish catch. The objective of this research is to derive an operational model, which can be used to analyse the performance of the fisheries under different simulated alternatives conditions. of techno-economic and biological Functions and parameters of a Base Model were estimated by deriving two sub-models: (a) bio-economic production and (b) the market, using regression techniques. Both primary and secondary data were used for empirical estimation of the sub-models. Accordingly, the model was developed, in a linear programming (LP) framework, to represent various fisheries in the riverine waters of Bangladesh. Results of the base model suggest that the riverine fisheries of Bangladesh are capable, under optimal conditions, of generating a total net benefit of BOT (Bangladesh Taka) 1,383 million per annum (US$1 = BDT32), of which 96% as producer surplus. Also, a significant overcapacity (118%) exists in the existing fleet in terms of application of effort relative to the resource availability. simulation of cost and demand changes reveal that the effect of changes in the cost condition of harvest will in general be related negatively to the intensity of total effort use, total langings, benefits and costs; while the effects of changes in the aggregate demand on total effort, total costs, landings, prices and net benefits will be positive. The implication of the results for management is that intervention into the fisheries through control on effort intensity would produce substantial net benefits from the open-water fisheries.